Desenvolvimento de um sistema de pedais dinamométricos para avaliação biomecânica no ciclismo - Carpes, Felipe Pivetta (2006)
The assessment of pedal forces is one of the more sophisticated methods applied on the sports sciences to accomplish cycling performance tests. With information of pedal forces the pedaling technique is evaluated based on the ability of the cyclists to produce and apply forces on the pedals. Several variables concerning the performance can be monitored with the application of instrumented pedals, but there is a lack of studies that consider the differences between the lower limbs on the force generation, what can occur due instrumentation limitation on the laboratories because the instrumented pedal are not commercial available and it is manufactured by research laboratories. The purpose of this study was to develop an instrumented pedals system that permit the evaluation of the pedal forces for each lower limb, with characteristics that no modify the normal pattern of pedaling and able to be used on different bicycle geometries and cycle ergometers. For the instrumentation, spindles of two (right and left) Shimano SPD pedals were modified to mounting 8 strain-gage sensors on each spindle, disposed on two rows and connected on two Wheatstone complete-bridges to measure strain in response to horizontal (Fx, tangential bridge) and vertical loads (Fz, normal bridge). With the spindles mounted on the pedal body, a piece for connection with the crank was manufactured. These pieces (right and left) are the house for ball bearings that permit the movement of the pedal relative to crank and not commit the strain-gages wires. These pieces permit the application of the pedal on different bicycles and cycle ergometers. The system was calibrated and presents a linear relationship between the load applied and the signal output from the full-bridges that monitor the horizontal and vertical efforts on the spindles. A calibration matrix was developed to transform the output signal to force magnitudes, and also an interference matrix was mounted to correct the mechanical interference between the horizontal and vertical measures. For the two pedals, the hysteresis was lower than 0,60%. For the right pedal, the sensitivity of the normal bridge was 2.5 mV/N, the tangential bridge present sensitivity of 2.6 mV/N. The left pedal presents a sensitivity of 2.4 mV/N and 2.7 mV/N for normal and tangential bridges, respectively. The resolution of the system was, for both pedals, lower than 0.5 N, while the error calculated from the calibrated data was 1% for the right normal bridge and 2% for the right tangential bridge and left normal and tangential bridges. It can be concluded that the system present characteristics that permits the application on the athlete s evaluations due the low error, satisfactory resolution and good linearity observed between the applied loads and the signal output on the normal and tangential full-bridges.